PENGARUH PENGGUNAAN STRATEGI SHARING TASK DAN JUMPING TASK DALAM LESSON STUDY TERHADAP HASIL BELAJAR FISIKA SMA - Sariyati, Eka; Suseno, Nyoto; Alarifin, Dedy Hidayatullah (Universitas Muhammadiyah Metro, 2022)
ABSTRACT: The lack of student learning activities has an effect on the low learning outcomes. The purpose of this research is to know the effect of sharing task and jumping task to learning result and advantages and disadvantages of sharing task and jumping task. The sample in this study X IPA.4 experimental class and X IPA.1 control class. Quasi experimental research method with posttest-only control design. Analysis of quantitative data using two difference test of average at 5% significance level obtained tcount (1,6999)> ttabel (1,682). The use of sharing task and jumping task has an effect on student learning outcomes. It can be suggested for teachers to apply the task sharing strategy and jumping task to learning activitiesKeywords: Sharing Task and Jumping Task, Lesson Study, Learning Outcomes.